First record of \(Limnonectes fastigatus\) Stuart, Schoen, Nelson, Maher, Neang, Rowley & Mcleod, 2020 (Anura: Dicroglossidae) from Vietnam - The Pham, Cuong; Duc Le, Minh; Thi Ngo, Hanh; Ziegler, Thomas; Quang Nguyen, Truong (Academia Journal of Biology, 2022)
We record Limnonectes fastigatus for the first time from Vietnam based on a new amphibian collection from Chu Mom Ray National Park, Kon Tum province. Morphological characteristics of the specimens from Chu Mom Ray National Park resemble those of the type series from Cambodia. The specimens from Vietnam differ from the type series from Cambodia by having a slightly larger size in males and a distinct colour pattern on the dorsum. Genetic divergences between sequences of the Vietnamese specimens and those of Limnonectes fastigatus from Cambodia available from GenBank are 2.0–2.1% (16S gene). In addition, we provide morphological data and natural history notes of the aforementioned species from Vietnam.